Genetic Relationships between Clinical Isolates of Streptococcus pneumoniae, Streptococcus oralis, and Streptococcus mitis: Characterization of “Atypical” Pneumococci and Organisms Allied to S. mitis Harboring S. pneumoniae Virulence Factor-Encoding Genes - Whatmore, Adrian M. (American Society for Microbiology, 2000)
The oral streptococcal group (mitis phylogenetic group) currently consists of nine recognized species, although the group has been traditionally difficult to classify, with frequent changes in nomenclature over the years. The pneumococcus (Streptococcus pneumoniae), an important human pathogen, is traditionally distinguished from the most closely related oral streptococcal species Streptococcus mitis and Streptococcus oralis on the basis of three differentiating characteristics: optochin susceptibility, bile solubility, and agglutination with antipneumococcal polysaccharide capsule antibodies. However, there are many reports in the literature of pneumococci lacking one or more of these defining characteristics. Sometimes called “atypical” pneumococci, these isolates can be the source of considerable confusion in the clinical laboratory. Little is known to date about the genetic relationships of such organisms with classical S. pneumoniae isolates. Here we describe these relationships based on sequence analysis of housekeeping genes in comparison with previously characterized isolates of S. pneumoniae, S. mitis, and S. oralis. While most pneumococci were found to represent a closely related group these studies identified a subgroup of atypical pneumococcal isolates (bile insoluble and/or “acapsular”) distinct from, though most closely related to, the “typical” pneumococcal isolates. However, a large proportion of isolates, found to be atypical on the basis of capsule reaction alone, did group with typical pneumococci, suggesting that they have either lost capsule production or represent as-yet-unrecognized capsular types. In contrast to typical S. pneumoniae, isolates phenotypically identified as S. mitis and S. oralis, which included isolates previously characterized in taxonomic studies, were genetically diverse. While most of the S. oralis isolates did fall into a well-separated group, S. mitis isolates did not cluster into a well-separated group. During the course of these studies we also identified a number of potentially important pathogenic isolates, which were frequently associated with respiratory disease, that phenotypically and genetically are most closely related to S. mitis but which harbor genes encoding the virulence determinants pneumolysin and autolysin classically associated with S. pneumoniae.